Serum Leptin Levels in Women with Immunological Recurrent Abortion - S Zarei; H Soltanghoraee; A Mohammadzadeh; S Arefi; AH Zarnani; F Idali; B Tavangar; E Savadi-Shiraz; N Moshref Behzad; M Jeddi-Tehrani (JRI, 2010)
Introduction: Recurrent abortion (RA) may be a consequence of aberrant expression of immunological factors during pregnancy. Although the relative importance of immunological factors in human reproduction remains controversial, substantial evidence suggests that autoantibodies contribute to reproductive failure. Production of such antibodies is under the control of cytokines; and leptin, besides its role in reproductive success, has a profound effect on directing the cytokine profile toward Th1 (cellular) pattern. Therefore, the present study was performed to assess serum leptin levels in women with immunological recurrent abortion.Materials and Methods: In this prospective study, 250 women who attended Avicenna Infertility Clinic with RA were screened for known causes of abortion from July to December 2008 in Tehran, Iran. Eighty-one patients with normal karyotypes and hormonal profile with normal ovaries and uterus and no signs of infection were categorized as patients with immunological (IRA, n = 39) or unexplained (URA, n = 42) recurrent abortion based on presence or absence of autoantibodies. After blood sampling, levels of anti-nuclear antibody (ANA), anti-double stranded DNA antibody (anti-dsDNA), lupus anti-coagulant antibody (LACAb), anti-phospholipid antibody (APA), anti-cardiolipin antibody (ACA), anti-thyroglobulin antibody (TgAb), anti-thyroperoxidase antibody (TPOAb) and anti-thrombin III antibody (ATIIIAb) were measured by enzyme-linked immunosorbent assay (ELISA) or chemiluminescent enzyme immunoassay (CLEIA).Results: In IRA group, 9 (23.1%), 24 (61.5%), 25(64.1%) and 1 (2.6%) women were above the normal cut-off point for ANA, TgAbs, TPOAbs and AT-III Abs, respectively. IRA patients had normal values of LACAbs, APA and ACA. With normal level of fasting blood sugar (FBS), IRA and URA groups had similar serum leptin levels (23.7  13.2 ng/ml vs. 22.7  12.5 ng/ml, respectively). Serum leptin concentrations showed a positive correlation with weight and BMI in both groups.Conclusion: This study suggests that serum leptin levels are higher in IRA and URA patients than normal women. The findings of this study suggest the need for a more comprehensive study and comparison of leptin levels in IRA and URA patients to women with no history of miscarriages.
Keywords: Autoantibody, Immunological, Leptin, Pregnancy, Recurrent abortion, Spontaneous abortion